Patient-Specific Computational Analysis of Hemodynamics and Wall Mechanics and Their Interactions in Pulmonary Arterial Hypertension - Zambrano, Byron A.; McLean, Nathan; Zhao, Xiaodan; Tan, Ju-Le; Zhong, Liang; Figueroa, C. Alberto; Lee, Lik Chuan; Baek, Seungik (Frontiers in Bioengineering and Biotechnology, 2021)
Vascular wall stiffness and hemodynamic parameters are potential biomechanical markers for detecting pulmonary arterial hypertension (PAH). However, the interaction between wall deformation and blood flow has not been fully understood. Here, we applied an established computational framework that utilizes patient-specific measurements of hemodynamics and wall deformation to analyze the coupled fluid-vessel wall interaction in the proximal pulmonary arteries of 6 PAH patients and 5 control subjects. Specifically, we quantified the linearized stiffness modulus (E), relative area change (RAC), diastolic diameter (D), PA regurgitant flow, and time averaged wall shear stress (TAWSS) of the pulmonary arteries, as well as the total arterial resistance (R_t) and compliance (C_t) at the distal PA vasculature. The study found that the average proximal PA diameter was larger (32 mm vs. 24 mm; p = 0.007), stiffer (E; 293 KPa vs. 68 KPa; p = 0.014) and had a reduced RAC (20% vs. 45%; P = 0.001) in the PAH group compared to the control group. Also higher R_t (7.67 mmHg x min/l vs 4.12 mmHg x min/l ; p=0.005) and lower C_t (0.14 ml/mmHg vs 0.72 ml/mmHg ; p=0.019) were found in the PAH group. Furthermore, it was observed that E was directly correlated to the PA regurgitant flow (r = 0.893, p=0.016) and inversely related to TAWSS (r=-0.746; p=0.088) in the PAH group. Results suggest that the estimated elastic modulus E may be closely related to PAH hemodynamic changes in pulmonary arteries.